KONTRIBUSI PEMANFAATAN LAHAN PEKARANGAN TERHADAP KEHIDUPAN SOSIAL EKONOMI KELOMPOK KEMBANG TANI DI DESA CUCUM KABUPATEN ACEH BESAR - Elly Susanti; Ahmad Humam Hamid; Nurul Hidayah (Fakultas Pertanian, Universitas Riau, 2017)
Yard area is an area of land that is in the front, rear and side of the house building which can be harnessed into productive land with socially economically functional outcome. The purpose of this study was to determine the utilization of yard area by commodity type and yard area contribution form to the social and economic life of Kembang Tani Group. This research was conducted at Cucum Village in Aceh Besar Regency by using census method. Data were analyzed using descriptive qualitative and quantitative approaches. The results showed that: (1) Utilization of yard area was mostly used for vegetables (water spinach, celery, spinach, mustard greens, lettuce), poultry (free-range chicken, duck laying hens and muscovy duck), fruits, fish (freshwater catfish, tilapia fish) and medicinal plants; (2) Social contribution form of giving (2,65%) and exchange (3,27%) with neighbors as well as giving to relatives (7,09%); (3) The economic value such as saving expense or non-cash income was on the low category of IDR 1.650.237/year or IDR 137.519/month and additional cash income was on medium category of IDR 28.876.183/year or IDR 2.406.348/month.